In Vitro Digestibility in Animal Nutritional Studies - Peiretti, Pier Giorgio (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book addresses various aspects of in vitro digestibility: • Application of meta-analyses and machine learning methods to predict methane production; • Methane production of sainfoin and alfalfa; • In vitro evaluation of different dietary methane mitigation strategies; • Rumen methanogenesis, rumen fermentation, and microbial community response; • The role of condensed tannins in the in vitro rumen fermentation kinetics; • Fermentation pattern of several carbohydrate sources; • Additive, synergistic, or antagonistic effects of plant extracts; • In vitro rumen degradation and fermentation characteristics of silage and hay; • In vitro digestibility, in situ degradability, and rumen fermentation of camelina co-products; • Ruminal fermentation parameters and microbial matters to odd- and branched-chain fatty acids; • Comparison of fecal versus rumen inocula for the estimation of NDF digestibility; • Rumen inoculum collected from cows at slaughter or from a continuous fermenter; • Seaweeds as ingredients of ruminant diets; • Rumen in vitro fermentation and in situ degradation kinetics of forage Brassica crops; • In vitro digestibility and rumen degradability of vetch varieties; • Intestinal digestibility in vitro of Vicia sativa varieties; • Ruminal in vitro protein degradation and apparent digestibility of Pisum sativum; • In vitro digestibility studies using equine fecal inoculum; • Effects of gas production recording system and pig fecal inoculum volume on kinetics; • In vitro methods of assessing protein quality for poultry; and • In vitro techniques using the DaisyII incubator.